Babur - Prose Writer, Master Of Portrait And Landscape - Kazakova Ra’no Mashrabayevna (Zien Journals, 2022)
This article discusses the problem of studying "Babur-name", the ideological and artistic features of the work, and also provides examples of the skill of Babur as a portrait and landscape painter.
Keywords: portrait; landscape; memoirs; studies